Coastal Geo-environmental Hazards and Its Management - , Subhankar Patra (Archives of Current Research International, 2017)
This paper assessed and cartographically analysed the impact of recent coastal geo-environmental hazards upon coastal resources and also human life. Cyclonic storms, high wave action, tidal bore, coastal flood and also coastal erosion are the main geo-environmental hazards over the Bay of Bengal coastal area especially Kanthi coastal tract of west Bengal. Sea surface temperature over a period of 50 years was observed through this study to be changing up to the magnitude of about 0.019°C/year over the Bay of Bengal between the period from 1972-2005. As a result accelerated trend for the genesis and favourable condition for the sever cyclone of 1978, 1988, 1989, 1995, 2009, 2010, 2011, 2012 and 2013 and local sea level has risen, on average 15 cm/last 3 decades. High wave action and coastal flood due to cyclonic storms and also high rainfall during the monsoon seasons (In record and evidence of highest sea gauge during the last 30 years generally increasing which relatively 2 m to 3 m) have been affected to coastal environment. On the other hand, coastal erosion is another geomorphic hazard identified in this study to be due to high wave action during the cyclonic period and also monsoonal season. In result about 25 m to 50 m/year coastal land has been eroded at Digha-Shankarpur and adjoining coastal tract. For this reason, the popular and famous beach tourism spot Digha-Mandarmoni of West Bengal has been extremely affected and also destroyed the gentle sea beach in recent time. Agricultural crops mainly food grains, vegetables, cashew nut, betelvine and many commercial crops and horticulture have been affected by the geo-environmental hazards of this area. So, resource depletion and resource crisis are the main problems of this area in recent time. Other hand the numerous number of geo environmental hazards through the year have been attacked to the coastal inhabitant. For the reason coastal people of the Kanthi coastal area has been suffering continually during the last 50 years. As a result thousands of people are environmentally refugee. So, it is right for the planning of coastal zone management by the proper and cartographic techniques.